Participation of Christian Higher Education in adults Education from Lecturers Perspective - Friandry Windisany Thoomaszen (Conference Series, 2020)
Lecturers as adult learners have challenges and barriers that are not easy to reach the quality of their personal growth and Christian Higher Education (CHE) as an organization. The study”s purpose is to understand lecturers’ perspectives about the CHE’s participation in adult education. Qualitative research was used in this study. The research subjects numbered 5 lecturers from one of the Christian campuses in Kupang City and were Protestant. Participants come from various gender, ethnic groups, ages, educational backgrounds, and work status of being a lecturer. The result of study find four themes related adults education in CHE, including the lecturer’s; need related formal and non-formal education; lecturer’s perspective about CHE’ participation in adults education; the barriers and cause of CHE’ participation in adults education; and lecturer’s suggestion for CHE to improve in adults education. Most of the five subjects agreed that non-formal education is more needed than formal education. The five subjects have strengths in the curiosity of learning, self-directedness behavior, and self-actualization. The limitation of this study is the lack of research subjects and diverse locations or diverse higher education, then further research can use a quantitative approach to investigate these problems. In conclusion, there are basic suggestions and barriers that CHE needs a lot of improvement about participation in adult education, especially related to growth mindset and grit; servant leader; and the alternative, emergent, organizational model.